Aplikasi Lembaga Pendidikan Este Pati Berbasis Web - Christinawati, Aulia, Aris Rakhmadi S.T, M.Eng (2017)
The purpose of the educational institution is educate children with affection to increase their knowledge and their intelligence. As informal institution, ESTE Pati needs a good work system and an information system academic to bring the purpose. Choosing the appropriate academic system information can fix the ineffectiveness of the manual academic system information which is still used in the educational institution of ESTE Pati. The purpose of this research is looking for the information in the educational institution of ESTE Pati and also to create the education tutoring and courses schedule, so that the schedules clash can be avoided. The development of this aplication educational institution is used PHP open source authoring term which will be called into aplication and using MySQL database and it will be built in the form of website. This aplication can help the administration of educational easier in operating the website, it is written with 10 respondents by way the amount of 50% help aplicants look for the information and it can be a good value added for the educational institution of ESTE Pati.